The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijms21041325
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Allium Crops Bulb Enlargement in Response to Photoperiod: A Review

Abstract: The photoperiod marks a varied set of behaviors in plants, including bulbing. Bulbing is controlled by inner signals, which can be stimulated or subdued by the ecological environment. It had been broadly stated that phytohormones control the plant development, and they are considered to play a significant part in the bulb formation. The past decade has witnessed significant progress in understanding and advancement about the photoperiodic initiation of bulbing in plants. A noticeable query is to what degree th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 242 publications
0
12
0
1
Order By: Relevance
“…Sucrose is also the most abundant soluble carbohydrate in most onion cultivars (Pöhnl et al 2018). In recent research, carbohydrates were reported to be a factor influencing the bulb initiation and growth of Allium species (Atif et al 2020). A previous study also reported that abiotic stress tolerance in plants, especially drought tolerance, is correlated with carbohydrate metabolism.…”
Section: Carbohydratesmentioning
confidence: 99%
“…Sucrose is also the most abundant soluble carbohydrate in most onion cultivars (Pöhnl et al 2018). In recent research, carbohydrates were reported to be a factor influencing the bulb initiation and growth of Allium species (Atif et al 2020). A previous study also reported that abiotic stress tolerance in plants, especially drought tolerance, is correlated with carbohydrate metabolism.…”
Section: Carbohydratesmentioning
confidence: 99%
“…The effect of gibberellin on allium species, including onions and garlic has been reported in several papers (Geetharani et al, 2008;Ouzounidou et al, 2011). Currently, the application of gibberellin is considered as a new technique for enhancing the yield and improving propagation competence in garlic (Atif et al, 2020). The response of different organs of plants to the changes in gibberellin content is not similar since distinct parts of plants do not have the same sensitivity to this hormone (Martins et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Bulbs of F. meleagris, regenerated in vitro, also become dormant and cease growing, sprouting and forming leaves, if they had not been exposed to low temperature treatment [5]. Fritillary bulbs in vitro were inadequate for further morphogenesis if it was warm (24 • C) through the whole monitored period, similarly to many other geophytes [10]. Bulb regeneration in onion is well documented and controlled by day length and plant growth regulators (PGR), where gibberellic acid (GA 3 ) is crucial in this process [11,12].…”
Section: Introductionmentioning
confidence: 99%